Method for measuring dissolved hydrogen in anaerobic ecosystems: application to the rumen. - Robinson, J A (1981)
A method of transferring dissolved H2 to a CO2 headspace and then absorbing out the CO2 to concentrate the H2 before gas chromatographic analysis was developed to measure low concentrations of dissolved H2. A detection limit of 10 pmol of H2 ml-1 of water was achieved. When used ot monitor H2 changes in a bovine rumen, a 10-fold increase in H2 was noted 1 h after feeding and then declined rapidly to the normal steady-state concentration of 1 microM.